(untitled) (Fiep Bulletin - online, 2013)
The vascular ulcer is a syndrome characterized by loss of tegument (dermis or epidermis) and may spread to subjacent and subcutaneous tissues, where it attacks lower limb extremities. Its cause is generally related to the arterial vascular and/or venous system. Its frequency is increasing with the increase of life expectancy of the world population. This descriptive study conducted in the sector of the curative clinic of a University Hospital in Natal/RN aimed to characterize the assistance to elderly people with vascular ulcer. The population was composed of 32 elderly patients with vascular ulcers guided by the arms clinic. Used as a source of the data records of patients and a structured form. The search returned a favorable opinion (No. 54/05) of the Ethics Committee of UFRN. Data were transferred to Excel 2000 and analyzed in SPSS 14.0. The conduct in the home treatment was adequate in 62.5%, 31.3% did not hold regular treatment, 68.8% had inadequate follow-up clinical; the systemic treatment was inadequate in 56.3%, 31.3% had no compression therapy, and 59.4% was inappropriate; adequate home dressing kit in 53,1%; monitoring the health professional, USB/home was inadequate in 81.3%; 81.3% was present in the training for the conduct of dressing; the quality of care was considered inadequate in 71.9%.Assistance to holders of UV is usually complex, long and requires interdisciplinary expertise, specific knowledge, technical skills, links between the levels of complexity for assistance and also active participation of the bearer and their families, within a holistic approach. The results show that when these factors are adequate, influence satisfactorily the healing of the injury.